Implementation of Customer Relationship Management to Improve Financing Products - Chaidir Iswanaji; Khairul Ikhwan; Muhamad Wahyudi; Ayunda Putri Nilasari; Siti Rokhaniyah (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
The banking world has also now begun to experience the development of digital technology. Digital banking was created to improve the quality of service to be more efficient and effective for customers. The purpose of this research is to assess the implementation of Customer Relationship Management (CRM) to increase financing product at Bank Syariah Indonesia (BSI). This research uses a qualitative approach with primary data obtained through observation and interviews, as well as secondary data from BSI-related documents. CRM implementation can increase the amount of financing, especially for multi-purpose financing products. CRM implementation is a strategy to increase customer loyalty, which can ultimately improve company performance. Islamic banking needs to implement CRM in order to establish good communication with customers, thereby supporting the achievement of sustainable performance. The sample of this study is limited to BSI branch offices in Sleman and Magelang. Further research can expand the number of research samples to sharpen the data analysis about CRM implementation in BSI. Further research can expand the perspective of data analysis to obtain information about CRM implementation in BSI more broadly.